Gestão dos resíduos sólidos das contruções prediais na cidade do Natal-RN - Silva Filho, Alcides Fernandes e (2005)
The present work has the objective of presenting an investigation about the quantification, classification and destination of the waste of construction and demolition (RCD) in the city of Natal - RN, focusing the aspects of the environmental impacts and the strategic importance of the environmental administration in the earnings of productivity of the companies. Of the environmental point of view the research intends to identify and to quantify the monthly and annual production of RCD in the city, as well as to know the places of deposition of those residues. To reach the objectives of the study, an exploratory and descriptive research was accomplished, using a questionnaire with closed subjects and an open one, applied in 25 entrepreneurs of the branch of the building site, being 21 builders and 4 entrepreneurs of collection companies and removal dumps. As form of analysis of the data, the descriptive analysis was used and of crossing. The production engineering considers important the insert of best production practices and administration of the product in the companies, with views to the increase of your competitiveness, productivity earnings and improvement of the environmental aspects with views to the consumer's satisfaction, in that case the buyer of immobile. The principal results of the investigation demonstrate that there was not great variability of answers with relationship to the interviewees opinion in what he refers to the environmental practices. In your majority the building site interviewees entrepreneurs evidenced the absence of the public power, particularly the city hall of Natal, in the control, fiscalization and creation of mechanisms for a correct destination of RCD, as well as for your reuse and recycle. On the other hand also it was evident that the recycle or the reuse of RCD on the part of the companies is a rare practice and a lot of times inexistent, although the entrepreneurs' of the building site section great majority recognizes that would have won of productivity with the correct and intensive use of such measures